Effective Biofilm Eradication on Orthopedic Implants with Methylene Blue Based Antimicrobial Photodynamic Therapy In Vitro - Julia Prinz; Marianne Wink; Sonja Neuhaus; Markus C. Grob; Heinrich Walt; Philipp P. Bosshard; Yvonne Achermann (Antibiotics, 2023)
Periprosthetic joint infections (PJI) are difficult to treat due to biofilm formation on implant surfaces, often requiring removal or exchange of prostheses along with long-lasting antibiotic treatment. This in vitro study investigated the effect of methylene blue photodynamic therapy (MB-PDT) on PJI-causing biofilms on different implant materials. MB-PDT (664 nm LED, 15 J/cm2) was tested on different Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli and Cutibacterium acnes strains in both planktonic form and grown in early and mature biofilms on prosthetic materials (polyethylene, titanium alloys, cobalt–chrome-based alloys, and bone cement). The minimum bactericidal concentration with 100% killing (MBC100%) was determined. Chemical and topographical alterations were investigated on the prosthesis surfaces after MB-PDT. Results showed a MBC100% of 0.5–5 μg/mL for planktonic bacteria and 50–100 μg/mL for bacteria in biofilms—independent of the tested strain, the orthopedic material, or the maturity of the biofilm. Material testing showed no relevant surface modification. MB-PDT effectively eradicated common PJI pathogens on arthroplasty materials without damage to the materials, suggesting that MB-PDT could be used as a novel treatment method, replacing current, more invasive approaches and potentially shortening the antibiotic treatment in PJI. This would improve quality of life and reduce morbidity, mortality, and high health-care costs.